2020
DOI: 10.1177/0300060520918697
|View full text |Cite
|
Sign up to set email alerts
|

Novel “all-in-one” sandwich technique for reconstruction of full-thickness defects of the lower eyelid: a case report

Abstract: The current paper presents a case report of lower eyelid reconstruction after removal of a basal cell carcinoma. Our novel reconstruction method consists of translation and rotation of a paramedian forehead flap into the defect, conjunctivorhinostomy for reconstruction of the nasolacrimal duct, and placement of a sandwich ear cartilage graft that is primarily seated into the forehead flap to maintain the vertical dimension of the eyelid. This “all-in-one” technique has the advantage of one-step reconstruction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Sensory loss at the forehead has been reported to be temporary due to the overlapping adjacent supraorbital nerve territory [ 16 ]. Lower eyelid retraction with inferior scleral show has also been reported [ 24 ]. Lagophthalmos was the most common complication noted within our case series, which is not widely reported in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…Sensory loss at the forehead has been reported to be temporary due to the overlapping adjacent supraorbital nerve territory [ 16 ]. Lower eyelid retraction with inferior scleral show has also been reported [ 24 ]. Lagophthalmos was the most common complication noted within our case series, which is not widely reported in the literature.…”
Section: Discussionmentioning
confidence: 91%
“… 11 and Elshamma et al ., 12 many authors describe the use of this local flap for reconstruction of medially located eyelid defects or defects of the medial canthus. Modifications of this technique for periocular reconstruction, such as expanded pedicled forehead flaps, 14 single-staged tunnelled forehead flaps, 15 or forehead flaps with implantation of a chondral graft 16 have been described too. Nevertheless, no comparable articles using the same combination of reconstructive techniques as described in this case report could be revealed by our Pubmed.gov search.…”
Section: Discussionmentioning
confidence: 99%
“…Auricular cartilage has been published widely as an available substitute of defected tarsus to restore stability of the lower eyelid (42). Fodor et al (48) reported a novel "allin-one" sandwich technique to reconstruct a full-thickness defect of the lower eyelid after removing a basal cell carcinoma. They placed a sandwich ear cartilage graft into a paramedian forehead flap and rotated it into the defect site, which helps maintain the eyelid's vertical dimension.…”
Section: Auricular Cartilagementioning
confidence: 99%